A case study on the design of a barrier-free environment for a Filipino wheelchair-bound entrepreneur - Elamparo, Childy R.
This thesis is a case study which sought to provide a design layout of an ideal home environment for a Filipino female wheelchair-bound entrepreneur who operates a bake shop located in her residence. The existing conditions of the spaces in her home include barriers and limitations to her accessibility to and from her work areas. The study adapted the theory on Barrier-Free Design to come up with a proposed model floor plan addressing the needs of the chosen female wheelchair-bound entrepreneur. Forms of instrumentation utilized in the data gathering include site visits, photo documentation, interview, and ocular observations. Analysis of the data was made by applying the narrative, tabulation and design programming methods. Based on the findings, several diagrams were developed namely proximity, bubble and schematic diagrams which equipped the researcher in coming up with the best layout for a wheelchair bound entrepreneur whose business is located in her residence. The development of the design was based on the needs and preferences of the user which surfaced during the researcher's interview with her and during the conducted ocular observations and site visits to the home. The proposed model included a floor plan, kitchen elevations and, toilet and bath elevations which applied design considerations for a barrier-free home environment. Results indicated that the subject's bedroom should be relocated from the second floor to the ground floor in order to allow easy access for the subject when she travels from her room to the kitchen where she works frequently. The kitchen, bake shop and, toilet and bath were found to have major design flaws such as high counters, narrow doors, worn out tiles and poor accessibility among the areas.